2020
DOI: 10.1055/s-0039-1692323
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Hand Infections in an Underserved Population: The Role of Diabetic Status in Antibiotic Choice and Infection Location

Abstract: Introduction Patients with diabetes mellitus (DM) in underserved communities are at greater risk for hand infections. We aimed to describe the features of hand infections presenting to an urban hospital via laboratories, microbiology, and antibiotic choice with respect to diabetic status. Materials and Methods Patients presenting with any hand infection were reviewed and stratified by DM status and infection location. Labs, culture results, antibiotic regimens, and significant predictors of laboratories or inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…These results hold considerable clinical importance for those patients at higher risk for infection and with more devastating complications of inadequate treatment, as patients with diabetes may have up to a 39 % chance of amputation after developing an upper extremity infection that requires operative debridement (Gonzalez et al, 1999). Prior research has demonstrated that patients with diabetes have elevated baseline ESR and CRP compared to non-diabetics, yet WBC and CRP recently have been shown to be comparable in diabetics and non-diabetics with hand infections (Hayden et al, 2020). For diabetic hand infections involving an abscess, prompt recognition followed by timely surgical debridement and initiation of appropriate antibiosis is imperative (Jalil et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These results hold considerable clinical importance for those patients at higher risk for infection and with more devastating complications of inadequate treatment, as patients with diabetes may have up to a 39 % chance of amputation after developing an upper extremity infection that requires operative debridement (Gonzalez et al, 1999). Prior research has demonstrated that patients with diabetes have elevated baseline ESR and CRP compared to non-diabetics, yet WBC and CRP recently have been shown to be comparable in diabetics and non-diabetics with hand infections (Hayden et al, 2020). For diabetic hand infections involving an abscess, prompt recognition followed by timely surgical debridement and initiation of appropriate antibiosis is imperative (Jalil et al, 2011).…”
Section: Discussionmentioning
confidence: 99%